Undiagnosed cognitive impairment, health status and depressive symptoms in patients with type 2 diabetes - Koekkoek, Paula S.; Biessels, Geert Jan; Kooistra, Minke; Janssen, Jolien; Kappelle, L. Jaap; Rutten, Guy E H M (Elsevier, 2015)
Aims Type 2 diabetes (T2DM) is associated with cognitive impairment. We examined whether undiagnosed cognitive impairment in T2DM-patients is associated with a reduced health status and depressive symptoms. Methods In an observational study, 225 T2DM-patients aged < 70 years were examined at their homes and (some of them) at a memory clinic for undiagnosed cognitive impairment (dementia or mild cognitive impairment [MCI], defined according to internationally accepted criteria). Questionnaires assessing health status (SF-36, EQ-5D, EQ-VAS) and depressive symptoms (CES-D) were filled out. Health status and depressive symptoms were compared between patients with and without cognitive impairment. Results Patients with cognitive impairment (n = 57) showed significantly lower scores on the physical and mental summary scores of the SF-36 than patients with normal cognition (difference: 3.5 (95%-CI 0.7-6.3, p = 0.02, effect size 0.41) and 2.9 (95%-CI 0.3-5.6; p = 0.03, effect size 0.37). EQ-5D index and EQ-VAS scores were significantly lower in patients with cognitive impairment. Depression (CES-D < 16) occurred almost twice as often in patients with cognitive impairment (RR 1.8; 95%-CI: 1.1-3.0). Conclusions Undiagnosed cognitive impairment in T2DM-patients is associated with a reduced health status and more depressive symptoms. Detection of cognitive impairment in T2DM-patients identifies a vulnerable patient group that could benefit from tailored treatment and care.
Keywords: Cognitive impairment; Depressive symptoms; Elderly; Health status; Type 2 diabetes mellitus; Taverne; Endocrinology; Endocrinology, Diabetes and Metabolism; Internal Medicine